2023
DOI: 10.18632/aging.204583
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of immune cell infiltration for predicting immune escape and immunotherapy in cervical cancer

Abstract: The cervical cancer tumor microenvironment is a diverse and complex ecosystem. Tumor-immune cell infiltration (ICI) may influence immune escape and immunotherapeutic responses. However, the relationship between immune cell infiltrations, immune escape, and immunotherapy in cervical cancer has not been fully clarified. Here, Principal component analysis (PCA) and Tumor immune dysfunction and exclusion (TIDE) were applied to calculate individual ICI scores and probabilities of immune escape, respectively. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As described by previous studies, the results of immunotherapy were affected by the level of immune infiltration [ 14 ]. Therefore, we further assessed the prognosis value of FAO in immune therapy.…”
Section: Resultsmentioning
confidence: 99%
“…As described by previous studies, the results of immunotherapy were affected by the level of immune infiltration [ 14 ]. Therefore, we further assessed the prognosis value of FAO in immune therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The infiltration of immune cells is significantly related to the pathogenesis of cervical cancer [ 23 ]. By analyzing the TCGA dataset, we identified the infiltration of follicular helper T cells, natural killer cells, CD8 + T cells, mast cells, and Tregs associated with HIF-1A in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 The intricate mechanism responsible for the inherent system, suggesting that tumours possess mechanisms to evade immune surveillance. [21][22][23] Previous study has demonstrated that circPRDM4 participates in immune escape in hepatocellular carcinoma. 16 Thereafter, the role of circPRDM4 in the immune response of DDP-resistant CC cells was also explored for a better understanding of the phenomena of circPRDM4 on CC chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular immunity, particularly involving T lymphocytes, dendritic cells, natural killer cells and macrophages, plays a crucial role in anti‐tumour immune responses. Nevertheless, tumours can persist and metastasize despite the presence of a functioning immune system, suggesting that tumours possess mechanisms to evade immune surveillance 21–23 . Previous study has demonstrated that circPRDM4 participates in immune escape in hepatocellular carcinoma 16 .…”
Section: Discussionmentioning
confidence: 99%